The Legal Validity of the General Meeting of Shareholders Convened Pursuant to a District Court Order Subsequently Annulled by the Supreme Court - Young, James Tirtowijoyo; Dewanto, Wisnu Aryo (Dinasti Research, 2025)
This paper examines the legal paradox posed by the statutory finality of court orders authorizing the convening of General Meetings of Shareholders (GMS) under Article 80 (6) of Law No. 40 of 2007. Although the provision declares such orders is “final and has permanent legal force,” interpretive tension emerges where an order is issued ex parte in violation of the fundamental contradictory principle — notably audi et alteram partem — and subsequently annulled by the Supreme Court. Employing statutory, conceptual, and case-analysis approaches, the study analyzes the legal consequences of the landmark dispute concerning a GMS convened pursuant to District Court Order No. 1759/Pdt.P/2019/PN Sby, subsequently declared invalid ex post facto by Supreme Court Judgment No. 3241 K/PDT/2022. The inquiry contends that statutory finality is conditional rather than absolute, asserting that an order procured through procedurally defective proceedings is devoid of substantive legitimacy and may therefore be lawfully overturned. The Supreme Court’s annulment confirms that finality depends on observance of procedural guarantees and that annulment operates ex tunc, rendering resolutions adopted under the flawed Order void ab initio and stripping attendant notarial instruments of executorial force — with significant implications for corporate governance, registry practice, and the balance between legal certainty and due process.